The current increase and future perspectives of the microbial pesticides market in agriculture: the Brazilian example - Matheus Felipe de Lima Andreata; Silas Mian; Silas Mian; Galdino Andrade; Adeney de Freitas Bueno; Mauricio Ursi Ventura; José Eduardo Marcondes de Almeida; Eduardo Augusto Fonseca Ivan; Mirela Mosela; Mirela Mosela; Ane Stéfano Simionato; Renata Rodrigues Robaina; et al. (Frontiers in Microbiology)
The Brazilian agricultural sector contributes 25% to the national gross domestic product (GDP) and accounts for 49% of the country’s exports, faces significant challenges associated with tropical agriculture. Pests and diseases are major issues that compromise the productivity of various crops. In response, microbial pesticides have increasingly been incorporated as a component of integrated pest and disease management (IPM and IDM, respectively). This study presents a comprehensive analysis of the Brazilian biopesticide market, focusing on bioinsecticides, bionematicides, and biofungicides. Microbial agents, such as Bacillus spp., Trichoderma spp., and Beauveria spp., play a important role in IPM and IDM strategies, acting through multiple biocontrol mechanisms. The biopesticide market in Brazil has grown rapidly, driven by increased adoption by farmers and recent regulatory advances that have facilitated these products’ registration and commercialization process. Projections indicate that this sector will continue to grow in the coming years, supported by research innovations, consolidating biopesticides as key elements in Brazil’s transition to more sustainable agriculture. This review explores the challenges, opportunities, and future trends of microbial pesticides in Brazilian agriculture, highlighting their potential in increasing crop resilience and productivity while reducing the environmental impact associated with conventional pesticides.